The Correlation Between Tuberous Sclerosis Complex Genotype and Renal Angiomyolipoma Phenotype - Zhang, Nianyi; Wang, Xiaofang; Tang, Zengqi; Qiu, Xiaonan; Guo, Zhixuan; Huang, Danqi; Xiong, Hui; Guo, Qing (Frontiers in Genetics, 2021)
Tuberous sclerosis complex (TSC) is a rare multisystem autosomal dominant genetic disease that occurs between 1 in 6000 and 1 in 10000. Additionally, renal angiomyolipoma is the most common form of renal disease in patients affected by TSC. Although genetic mutation analysis of TSC is not rare, the correlation between TSC gene mutation and renal angiomyolipoma phenotype is poorly understood. This study aimed to analyze the mutation sites in 261 types of selected TSC patients. The results revealed that: 1) female patients developed more renal angiomyolipoma than male patients [p=0.008, OR=2.474, 95%CI (1.258-4.864)]; 2). missense mutation of TSC1 led to higher risk of renal angiomyolipoma [p<0.01, OR=15, 95%CI(2.859-78.691)], and in contrast, showed reduced risk in patients with frameshift mutation [P = 0.03, OR = 0.252, 95% CI (0.07-0.912)]; 3). patients with TSC2 mutations in the transcription activation domain 1 coding genes resulted in increased renal angiomyolipoma [p=0.019, OR=3.519, 95%CI(1.226-10.101)]. Therefore, our genotype-phenotype correlation study might shed light on early monitoring and evaluation of renal angiomyolipoma in TSC patients.